Teacher education and multicultural courses in North Carolina. Issue 2 (10th June 2019) - Williams III, John Andrew; Glass, Tehia Starker
Abstract : Purpose: Teacher effectiveness in diverse school environments depends highly on the multicultural education courses provided by Educator Preparation Programs (EPP). Research measuring new teachers' (i.e. teachers having 0-3 years of teaching experience) effectiveness as a result of EPPs' multicultural education courses is limited. The purpose of this study was to examine if any association occurred between the number of multicultural courses offered to pre-service teacher candidates by EPPs and their graduates rating of effectiveness, as it pertains to creating a culturally diverse classroom environment. Design/methodology/approach: Using data from the North Carolina Department of Public Instruction (NCDPI) and public EPPs course catalogs for North Carolina, this descriptive study investigates multicultural education course offerings and recent teacher graduate data for North Carolina for 2015, as it pertains to creating culturally diverse learning environments for students of color. Findings: The results indicate that multiple EPPs in North Carolina are not providing multicultural courses for their pre-service teachers, and that novice teachers in North Carolina are lacking the ability to produce diverse learning environments for students of color at a high capacity as defined by the North Carolina Teacher Effectiveness definition. Research limitations/implications: Data were retrieved from 2015. In the current year, EPPs could have boosted their offerings of multicultural courses since that time. Social implications: It is anticipated that the lack course offerings by EPPs will directly reflect new teachers' ability to create respectful learning environment for students of color, suggesting that EPPs may be counterproductive towards teacher candidates' understanding of race in the classroom. Originality/value: This study's originality exists in its ability to begin to connect new teachers' productivity with regards for promoting diversity or multiculturalism and the multicultural courses offered by EPPs.